2021
DOI: 10.7717/peerj.12510
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid promotes osteoclasts ferroptosis by inhibiting FBXO9-mediated p53 ubiquitination and degradation

Abstract: Bisphosphonates (BPs)-related osteonecrosis of jaw (BRONJ) is a severe complication of the long-term administration of BPs. The development of BRONJ is associated with the cell death of osteoclasts, but the underlying mechanism remains unclear. In the current study, the role of Zoledronic acid (ZA), a kind of bisphosphonates, in suppressing the growth of osteoclasts was investigated and its underlying mechanism was explored. The role of ZA in regulating osteoclasts function was evaluated in the RANKL-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In recent years, F-box proteins have been identified as essential factors for malignancies via target degradation ( 12 , 28 ). FBXO9 is a mysterious member of the F-box protein family ( 16 ), and a few available studies have shown that FBXO9 is involved in the development of the nervous system or adipose tissue ( 17 , 18 ), in pathological changes in the muscle in diabetes ( 17 ) and epithelial damage in respiratory distress syndrome ( 18 ), and in the adverse effects of zoledronic acid ( 19 ) or as a target of sepsis ( 18 ), and participates in disease progression in hematological tumors by regulating the activity of the mTOR pathway ( 20 ) and the proteasome ( 8 ). However, the biological functions and mechanisms underlying the role of FBXO9 in HCC have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, F-box proteins have been identified as essential factors for malignancies via target degradation ( 12 , 28 ). FBXO9 is a mysterious member of the F-box protein family ( 16 ), and a few available studies have shown that FBXO9 is involved in the development of the nervous system or adipose tissue ( 17 , 18 ), in pathological changes in the muscle in diabetes ( 17 ) and epithelial damage in respiratory distress syndrome ( 18 ), and in the adverse effects of zoledronic acid ( 19 ) or as a target of sepsis ( 18 ), and participates in disease progression in hematological tumors by regulating the activity of the mTOR pathway ( 20 ) and the proteasome ( 8 ). However, the biological functions and mechanisms underlying the role of FBXO9 in HCC have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, less attention has been paid to FBXO9 ( 16 ). To date, several substrates of FBXO9 have been identified, including Neurog2 ( 17 ), PRMT4 ( 18 ), p53 ( 19 ), PPARγ, BK channel β1 subunit, TEL2, and TTI1 ( 17 , 20 ). FBXO9 participates in several cellular processes by degrading these substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Iron ions is capable to induce OC differentiation and bone resorption through the production of ROS [ 48 , 49 ]. Zoledronic acid (ZA), a bisphosphonate, has been reported to inhibit OC growth via induction of ferroptosis of the OC [ 49 ].…”
Section: Ferroptosis and Bone Homeostasismentioning
confidence: 99%
“…Iron ions is capable to induce OC differentiation and bone resorption through the production of ROS [ 48 , 49 ]. Zoledronic acid (ZA), a bisphosphonate, has been reported to inhibit OC growth via induction of ferroptosis of the OC [ 49 ]. The role of ZA in regulating osteoclast function was evaluated using a RANKL-induced cell model, which indicated that ZA treatment suppressed the cell viability of osteoclasts and facilitated osteoclast ferroptosis with an increase in iron ions and ROS and decrease in the GPX4 and GSH level [ 49 ].…”
Section: Ferroptosis and Bone Homeostasismentioning
confidence: 99%
See 1 more Smart Citation